Is volumetric modulated arc therapy with constant dose rate a valid option in radiation therapy for head and neck cancer patients? - Didona, Annamaria (Rep Pract Oncol Radiother, 2018)
BACKGROUND: Intensity-modulated radiotherapy (IMRT) improves dose distribution in head and neck (HN) radiation therapy. Volumetric-modulated arc therapy (VMAT), a new form of IMRT, delivers radiation in single or multiple arcs, varying dose rates (VDR-VMAT) and gantry speeds, has gained considerable attention. Constant dose rate VMAT (CDR-VMAT) associated with a fixed gantry speed does not require a dedicated linear accelerator like VDR-VMAT. The present study explored the feasibility, efficiency and delivery accuracy of CDR-VMAT, by comparing it with IMRT and VDR-VMAT in treatment planning for HN cancer. METHODS AND MATERIALS: Step and shoot IMRT (SS-IMRT), CDR-VMAT and VDR-VMAT plans were created for 15 HN cancer patients and were generated by Pinnacle(3) TPS (v 9.8) using 6 MV photon energy. Three PTVs were defined to receive respectively prescribed doses of 66 Gy, 60 Gy and 54 Gy, in 30 fractions. Organs at risk (OARs) included the mandible, spinal cord, brain stem, parotids, salivary glands, esophagus, larynx and thyroid. SS-IMRT plans were based on 7 co-planar beams at fixed gantry angles. CDR-VMAT and VDR-VMAT plans, generated by the SmartArc module, used a 2-arc technique: one clockwise from 182° to 178° and the other one anti-clockwise from 178° to 182°. Comparison parameters included dose distribution to PTVs (D(mean), D(2%), D(50%), D(95%), D(98%) and Homogeneity Index), maximum or mean doses to OARs, specific dose-volume data, the monitor units and treatment delivery times. RESULTS: Compared with SS-IMRT, CDR-VMAT significantly reduced the maximum doses to PTV1 and PTV2 and significantly improved all PTV3 parameters, except D(98%) and D(95%). It significantly spared parotid and submandibular glands and was associated with a lower D(mean) to the larynx. Compared with VDR-VMAT, CDR-VMAT was linked to a significantly better D(mean), to the PTV3 but results were worse for the parotids, left submandibular gland, esophagus and mandible. Furthermore, the D(mean) to the larynx was also worse. Compared with SS-IMRT and VDR-VMAT, CDR-VMAT was associated with higher average monitor unit values and significantly shorter average delivery times. CONCLUSIONS: CDR-VMAT appeared to be a valid option in Radiation Therapy Centers that lack a dedicated linear accelerator for volumetric arc therapy with variable dose-rates and gantry velocities, and are unwilling or unable to sanction major expenditure at present but want to adopt volumetric techniques.